1988
DOI: 10.1128/jb.170.2.781-789.1988
|View full text |Cite
|
Sign up to set email alerts
|

Acinetobacter cyclohexanone monooxygenase: gene cloning and sequence determination

Abstract: The gene coding for cyclohexanone monooxygenase from Acinetobacter sp. strain NCIB 9871 was isolated by immunological screening methods. We located and determined the nucleotide sequence of the gene. The structural gene is 1,626 nucleotides long and codes for a polypeptide of 542 amino acids; 389 nucleotides 5' and 108 nucleotides 3' of the-coding region are also reported. The complete amino acid sequence of the enzyme was derived by translation of the nucleotide sequence. From a comparison of the amino acid s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
90
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(96 citation statements)
references
References 31 publications
4
90
0
2
Order By: Relevance
“…These were found in the gamma proteobacterium Acinetobacter sp. strain NCIB 9871 (3,16). They include the gene of the cyclohexanone monooxygenase (chnB) (3).…”
Section: Isolation Of Brevibacterium Epidermidis Hcumentioning
confidence: 99%
“…These were found in the gamma proteobacterium Acinetobacter sp. strain NCIB 9871 (3,16). They include the gene of the cyclohexanone monooxygenase (chnB) (3).…”
Section: Isolation Of Brevibacterium Epidermidis Hcumentioning
confidence: 99%
“…ChnB has high homology to a known cyclohexanone monooxygenase from Acinetobacter sp. strain NCIB 9871 (7,30). Accumulation of cyclohexanone as the major intermediate in the ChnB insertion mutant also confirmed that the enzymatic reaction catalyzed by the cyclohexanone monooxygenase was blocked in the ChnB mutant.…”
Section: Resultsmentioning
confidence: 56%
“…Two primers, monoL (GAGTCTGAGCATATGTCACAAAAAATGGATTTTG) and monoR (GAG TCTGAGGGATCCTTAGGCATTGGCAGGTTGCTTGAT), were designed based on the published sequence of the cyclohexanone monooxygenase gene of Acinetobacter sp. strain NCIB 9871 (7). PCR was performed in a Perkin-Elmer (Foster City, Calif.) GeneAmp9600.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations